Renovating My Academic Administration - Elizabeth Vander Lei (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
A department chair dons a hard hat and begins to see her position through the lens of spiritual rebirth and figured worlds—as a portrait of Calvin looks on.